German Norms of the Harvard Group Scale of Hypnotic Susceptibility, Form A (HGSHS:A) and Proposal of a 5-Item Short-Version (HGSHS-5:G). Issue 1 (2nd January 2021) - Riegel, Björn; Tönnies, Sven; Hansen, Ernil; Zech, Nina; Eck, Sandra; Batra, Anil; Peter, Burkhard
ABSTRACT: The Harvard Group Scale of Hypnotic Susceptibility, Form A (HGSHS:A), is commonly used to test hypnotizability. There is still some controversy about what exactly hypnotizability is and whether and how it can be measured, especially by the HGSHS:A. Furthermore, a wider clinical use is limited, requiring a testing time of more than 1 hour. We analyzed the German HGSHS:A version for its factorial structure, item contribution, and item difficulty based on test data from six studies, including 1276 persons, to propose a shorter version of the HGSHS:A. We hereby present a 5-item version of the HGSHS:A (HGSHS-5:G), consisting of the challenge items, that was compared with an 11-item version (highly variable posthypnotic amnesia omitted). Age- and gender-specific norms was generated. The HGSHS-5: G showed high validity, reliability, and classification agreement. It reduces test time to 30 minutes thus facilitating wider use of hypnotizability testing.